Influential Correlation Factor Of The Iva Test Result Towards The Woman Prisoners Of Ii A Class In Semarang - Agustin Rahmawati; Lia Mulyanti (Universitas Muhammadiyah Semarang, 2016)
Abstract. Cervix cancer is number one killing disease among women. Since 2008-2014, Central Java especially Semarang is the second highest prevalence of cervix cancer. Actually the early cervix cancer detection could be conducted through IVA test, because this sort of test is relatively fast and accurate in only one visit and treatment.Woman prisoners are groups of nondependent person and vulnerable in case of reproduction system. According to theobservation, the excessive prisoners and lack of officers would limit health/medical access to its inhabitants. This study employed analytic correlation design by using 44 woman prisoners in prison of IIA class in Semarang. Besides the datawas analyzed using SPSS for windows. The result of the study showed that 29.5% women were positively infected (bypositive result of IVA test). In other hand, there were 52.3% women having sexual intercourse less than 20 years old,65.9% women having sexual partner. Besides, 52.3% women experienced douching vagina, 59.1% women were multiparity obstetric, and 77.3% women did not have any cancer history in their family. Conclusion: There is relatively influential correlation between the age of first time having sexual intercourse, numbers of sexual partners, and obstetric history towards the result of IVA test.